Race characters : ethnic literature and the figure of the American dream - Rana, Swati (University of North Carolina Press, 2020)
"A vexed figure inhabits U.S. literature and culture: the visibly racialized immigrant who disavows minority identity and embraces the American dream. Such figures are potent and controversial for they promise to atone for racial violence and perpetuate an exceptionalist ideal of America. In this book, Swati Rana builds on studies of character and racial form and offers a new way to view characterization through racialization that creates, through literary analysis, a fuller social reading of race"--